2017
DOI: 10.14260/jemds/2017/473
|View full text |Cite
|
Sign up to set email alerts
|

Microneedling With Platelet-Rich Plasma Versus Microneedling With Topical 5% Minoxidil in Patients With Androgenetic Alopecia- A Comparative Study

Abstract: BACKGROUNDAndrogenetic alopecia (AGA) is the most common type of alopecia in men, which is an androgen mediated event. The FDA approved treatment for male AGA are Finasteride and Minoxidil. Platelet-rich plasma (PRP) is a newer method for the treatment of various types of alopecia by providing growth factors in stimulating dermal papilla associated stem cells. Minoxidil helps in new hair growth by causing vasodilatation of scalp blood vessels. Treatment with microneedling showed an accelerated response leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…25 Another study reported the comparison of microneedling+5% minoxidil treatment against microneedling+PRP, in that case, both treatments showed similar results been both effective in AGA treatment. 26…”
Section: Microneedlingmentioning
confidence: 99%
“…25 Another study reported the comparison of microneedling+5% minoxidil treatment against microneedling+PRP, in that case, both treatments showed similar results been both effective in AGA treatment. 26…”
Section: Microneedlingmentioning
confidence: 99%